The Quaternary in the tropics a reconstruction of the palaeoclimate - Heine, Klaus 1940-2023 (Springer textbooks in earth sciences, geography and environment, 2024)
The Ice Age (Quaternary) is a period of extreme climate fluctuations that led to the growth and melting of massive ice sheets in the high latitudes. Tropical deserts, savannas, rainforests, and mountainous regions experienced equal dramatic climatic changes of which the traces are preserved in sedimentary deposits. The knowledge of tropical climate history is of paramount importance because in the tropics and marginal tropics, natural and - more recently - human-induced processes significantly control global climate. Yet relatively few palaeoclimate records are known from these regions.This book presents the climate archives of the tropics and critically discusses their palaeoclimatic informative value. Based on decades of research the author demonstrates that a lack of geoecological knowledge leads to misinterpretations in modeling climate futures. The results presented here call for a correction of many widely held views about the role of atmospheric greenhouse gases in global warming over the past 150 years.The book is intended for natural scientists of all disciplines who are looking for a synopsis of the problem area "Our climate in the past, present and future in the tropics"